Analisis Efektivitas Simpeg Dalam Mewujudkan E-Government Pada Kantor Imigrasi Kelas II TPI Belawan - Benyamin Kali Patembal Harahap; Sjahril Effendy; Muis Fauzi Rambe (Mahesa Research Center, 2021)
Human Resources (HR) development through education and training is not effective in shaping the character of the technology-based State Civil Apparatus. Technology-based human resource development, the Ministry of Law and Human Rights (Kemenkumham) built a Personnel Management Information System (SIMPEG). This study aims to determine how the effectiveness of SIMPEG at the Regional Office of the Ministry of Law and Human Rights of North Sumatra and how to realize e-government at the Regional Office of the Ministry of Law and Human Rights of North Sumatra, precisely at the Class II Immigration Office of TPI Belawan. The research approach used is a qualitative approach, which focuses on problems that exist at the time of the research or actual problems, and describes the facts about the problem being investigated along with their interpretation. Based on the research, it is found that SIMPEG of the Ministry of Law and Human Rights in its implementation has not been effective in improving employee professionalism, has not been used in the context of assigning employees according to their competence, and has not been used in the context of making employee transfer decisions and making decisions for promotion. The use of the Ministry of Law and Human Rights Simpeg is one form of e-government implementation at the Ministry of Law and Human Rights, especially the Class II TPI Belawan Imgrasi Office, where all employment processes are carried out electronically through the Ministry of Law and Human Rights Human Rights Management Information System application.